RANCANG BANGUN APLIKASI PRESENSI DENGAN GLOBAL POTITIONING SYSTEM (GPS) BERBASIS ANDROID (Studi Kasus : PT. Perkebunan Nusantara VI Unit Usaha Kayu Aro) - Megi Pratama; Vera Irma Delianti (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to produce a solution to the simplification of attendance activities at PT. Perkebuan Nusantara VI of the Wood Law, to produce attendance applications on the Android platform and equipped with a website (web service) and Client-Server, this attendance application uses PHP programming, to produce attendance applications based on Android and generate attendance applications using a MySQL database. This research method is the Unified Modeling Language or UML, which is a visual modeling method that functions as a means of designing object-oriented systems using certain notations and some architects. This model uses an application that is on the target side (client) after getting a request from the tracker (server) then the client will ask for the coordinates of its position on the GPS (Global Positioning System), which will then be sent to the tracker (server). The results of this study, namely 1. This attendance system was developed using current technology such as Android, which allows the company to get a lot of benefits, because it will make it easier and faster for employees in terms of attendance. This also affects the reports that will be made by HRD, because the data in the system is neatly organized so that making reports will be very easy. In terms of designing an Android-based online attendance system, good methods and ongoing research are needed so that in the future this system can be useful for the company. 2. With this online attendance system, employees can optimize their work very well. Because the attendance system is very easy to access and time can be used efficiently. 3. With the GPS lock method used, employees who want to be absent must actually be in the work unit area.